PPKn Teachers’ Efforts in Understanding Students Through the Merdeka Belajar Curriculum - Akhmad Qomaru Zaman; Irnawati Irnawati; Pandu Rudy Widyatama (JED (Jurnal Etika Demokrasi), 2023)
The independent learning curriculum indirectly emphasizes contextual learning by strengthening the value of Pancasila ideology with the reality of students' daily lives. The efforts of PPKn teachers in knowing their students need to involve a planned and integrated identification process to see the development of their character. Research method is qualitative descriptive method with phenomenological approach. Analysis of the Role of PPKn Teachers in Understanding the Learning Characteristics of Students with the Independent Learning Curriculum shows that there are 40% of High School Teachers in Surabaya. Analysis of PPKn Teachers Knowing the Level of Student Understanding of the Material Taught shows the results of 40% of High School Teachers in Surabaya.